O uso da contabilidade de custos no processo de gestão das empresas prestadoras de serviços contábeis - Pinheiro, Maria José Sales (2007)
Increasing modifications in the current market environment, raised by the competition to which companies are submitted, demand managers to comprehend management general information, with enough quantity and quality to scaffold their daily decisions. In such context, the adoption of tools of cost that suitably ain the decision-making process is fundamental. Therefore, this master’s research aims to identify which tools of cost are used to manage accountability service companies in Ceara, in order to support the decision-making that can be the difference between to keep on or not in the market. To identify such tools, a survey was carried out with the Regional Council of Accountability – CRC (CE) related to the accountability constituted companies with juridical report in CRC (CE). The study was applie only to the large accountability service companies in Ceara – following CRC’s classification. To data collection it was applied a questionnaire – sent to companies by e-mail. The data obtained with the questionnaire were organized and they received managers do not know or do not use the tools of cost as a support to the decision-making process and, among the ones that use the tools, there is a predominance of costing tradicional tools. This study understands that the suitable non-utilization of tools available from cost Accountability and their inner information directly jeopardizes these companies’ profitability and even their surviving in the market, since the company does not gather the necessary competitiveness conditions.